2022
DOI: 10.3390/molecules27051749
|View full text |Cite
|
Sign up to set email alerts
|

Design of Oligourea-Based Foldamers with Antibacterial and Antifungal Activities

Abstract: There is an urgent need to develop new therapeutic strategies to fight the emergence of multidrug resistant bacteria. Many antimicrobial peptides (AMPs) have been identified and characterized, but clinical translation has been limited partly due to their structural instability and degradability in physiological environments. The use of unnatural backbones leading to foldamers can generate peptidomimetics with improved properties and conformational stability. We recently reported the successful design of urea-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In recent years, more membrane-active helical unnatural foldamers have been developed as antimicrobial agents. [91][92][93][94][95][96][97][98][99][100][101][102][103] These latest works involve helical b-peptides, peptoids, g-peptides, sulfono-g-AApeptides, oligoureas, and so on. 95 They next designed a/b-peptide analogues with different a/b-amino acid organizations by replacing a-amino acid residues with b-amino acid residues to generate aab, aaab and aabaaab repeating units.…”
Section: Biological Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, more membrane-active helical unnatural foldamers have been developed as antimicrobial agents. [91][92][93][94][95][96][97][98][99][100][101][102][103] These latest works involve helical b-peptides, peptoids, g-peptides, sulfono-g-AApeptides, oligoureas, and so on. 95 They next designed a/b-peptide analogues with different a/b-amino acid organizations by replacing a-amino acid residues with b-amino acid residues to generate aab, aaab and aabaaab repeating units.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…In recent years, more membrane-active helical unnatural foldamers have been developed as antimicrobial agents. 91–103 These latest works involve helical β-peptides, peptoids, γ-peptides, sulfono-γ-AApeptides, oligoureas, and so on.…”
Section: Applications Of Unnatural Helical Peptidic Foldamersmentioning
confidence: 99%
See 1 more Smart Citation
“…Their antimicrobial activity is correlated with their unique pattern of chemical structure that can be imitated in material design. Numerous natural AMPs are recorded and annotated, and the development of synthetic AMPs never ends ( Wang et al., 2016 ; Ramamourthy et al., 2020 ; Tallet et al., 2022 ). Their antifungal mechanisms involve pore formation, mannan-binding, nucleic acid, and cell wall inhibition ( De Cesare et al., 2020 ).…”
Section: Polymer-based Strategies In Fungal Disease Treatmentmentioning
confidence: 99%
“…In recent years, oligourea foldamers with the general formula [NHCH(R)CH 2 NHCO] n have gained much attention as structural and functional mimetics of peptides [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. It has been shown that oligoureas can mimic the helical secondary structure of peptides.…”
Section: Introductionmentioning
confidence: 99%